2017
DOI: 10.1002/2016je005167
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two poles: Toward understanding the presence, distribution, and origin of volatiles at the polar regions of the Moon and Mercury

Abstract: The Moon and Mercury both have permanently shaded regions (PSRs) at their poles, which are locations that do not see the Sun for geologically long periods of time. The PSRs of the Moon and Mercury have very cold temperatures (<120 K) and as a consequence act as traps for volatile materials. Volatile enhancements have been detected and characterized at both planetary bodies, but the volatile concentrations at Mercury's poles are significantly larger than at the Moon's poles. This paper documents the study of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 147 publications
(374 reference statements)
1
40
0
Order By: Relevance
“…After decades of exploration, the preponderance of data from a host of remote sensing and in situ investigations point toward an enrichment of volatiles at polar latitudes of Earth's moon (Lawrence, , and references therein). Attempts to map the abundance and geographic distribution of volatiles, in particular H 2 O water ice and its derivatives, have been made using orbital neutron spectroscopy as well as ultraviolet and infrared (IR) reflectance measurements.…”
Section: Introductionmentioning
confidence: 99%
“…After decades of exploration, the preponderance of data from a host of remote sensing and in situ investigations point toward an enrichment of volatiles at polar latitudes of Earth's moon (Lawrence, , and references therein). Attempts to map the abundance and geographic distribution of volatiles, in particular H 2 O water ice and its derivatives, have been made using orbital neutron spectroscopy as well as ultraviolet and infrared (IR) reflectance measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Impact craters over the lunar polar regions, if permanently shaded from direct sunlight, can act as cold traps where the physical temperature remains extremely low (for instance, mean temperature 50 K in; Paige et al, ), allowing volatiles such as water ice to remain stable over geological timescales (e.g., Arnold, ; Lawrence, ; Lucey, ). Recent remote‐sensing observations have provided multiple lines of evidence for the presence of lunar surface water (H 2 O) and hydroxyl (OH − ) that could originate from solar wind implantation, impact delivery, and the interior of the Moon (e.g., Li & Milliken, ; Lucey et al, ; Pieters et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these surficial deposits are not volumetrically significant from the viewpoint of resource usage. Therefore, the detection of a large quantity of water ice delivered by water‐bearing debris or meteorites within the permanently shadowed regions (PSRs) near the lunar poles has been, and remains, a high‐priority challenge in lunar science (for a review, the reader is referred to; Lawrence, ). Recently, two orbital miniature synthetic aperture radars (India's Chandrayaan‐1 Mini‐SAR and NASA's Lunar Reconnaissance Orbiter (LRO) Miniature Radio Frequency [Mini‐RF]) found a class of anomalous craters with high circular polarization ratio (CPR) only in their interior regions, but not exterior to their rims (Spudis et al, ; Spudis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relative purity of Mercury's water‐ice deposits, with less than about 5% silicates by volume (Butler et al, ), supports deposition over a short time interval (such as potentially by a single large impact) rather than a steady‐state process. Although evidence of water‐ice and other volatile enhancements has been found at the lunar poles (e.g., Colaprete et al, ; Fisher et al, ; Hayne et al, ; Schultz et al, ), the inferred concentrations of water ice are significantly lower than, and distribution of water‐ice patchier than, those at Mercury (e.g., Lawrence, ). The substantial differences between the water‐ice inventories observed in the polar regions of Mercury and the Moon could be explained by the lack of a recent, large, water‐delivering impact at the Moon.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that additional water-ice reserves may exist in small-scale cold traps distributed across rough, intercrater terrain in the polar regions Neumann et al, 2017;Rubanenko et al, 2018). enhancements has been found at the lunar poles (e.g., Colaprete et al, 2010;Fisher et al, 2017;Hayne et al, 2015;Schultz et al, 2010), the inferred concentrations of water ice are significantly lower than, and distribution of water-ice patchier than, those at Mercury (e.g., Lawrence, 2017). The substantial differences between the water-ice inventories observed in the polar regions of Mercury and the Moon could be explained by the lack of a recent, large, water-delivering impact at the Moon.…”
Section: Introductionmentioning
confidence: 99%